2022
DOI: 10.4081/qrmh.2022.10296
|View full text |Cite
|
Sign up to set email alerts
|

Views from the trenches: California family physicians’ challenges and resilience factors while providing patient care during the initial wave of COVID-19

Abstract: This study examined challenges and factors promoting resilience among 20 California family physicians (FPs) during the first six months of the COVID-19 pandemic. A subset of academic, community, and resident FPs who responded to an online survey also participated in a semi-structured interview that explored concerns, moral distress, burnout, resource needs, support systems, coping strategies, and motivation to continue caring for patients. Thematic analysis was used to identify common themes in participant int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…A previous study, predominantly involving doctors as participants, found that most respondents reported a significant increase in stress levels during the pandemic [33]. However, higher resilience was linked to reduced stress, anxiety, fatigue, and sleep disturbances, indicating that greater resilience and grit served as protective factors against personal and systemic stressors during the COVID-19 pandemic [33,34]. The MoCA scores reveal mild cognitive impairment across the group, with particular deficits noted in the language domain.…”
Section: Discussionmentioning
confidence: 81%
“…A previous study, predominantly involving doctors as participants, found that most respondents reported a significant increase in stress levels during the pandemic [33]. However, higher resilience was linked to reduced stress, anxiety, fatigue, and sleep disturbances, indicating that greater resilience and grit served as protective factors against personal and systemic stressors during the COVID-19 pandemic [33,34]. The MoCA scores reveal mild cognitive impairment across the group, with particular deficits noted in the language domain.…”
Section: Discussionmentioning
confidence: 81%
“…3 These themes were echoed in the present study and in the interviews performed with a subset of 20 respondents. 22 Strengths and Limitations:…”
Section: Discussionmentioning
confidence: 99%
“…20 Factors hypothesized in our study to contribute to providers' moral distress during the pandemic were based on the research team's experience, literature review 2,13,20,21 and our initial pilot interviews. 22 Identi ed factors were inadequate resources, working under conditions that posed risk to providers' and their families' lives, restricting patient visitors during end-of-life care, limited availability of personal protective equipment (PPE), and providing only virtual patient visits that might compromise quality of care. 20 As early as medical school, health professionals who experience higher moral distress tend to become more burnt-out.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, burnout leads to poorer client and provider outcomes, facilitating conditions for MHPs to exit the profession (Delgadillo et al, 2018 ). The COVID-19 pandemic further exacerbated the strain on healthcare workers, including MHPs (Fischer et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%